STUDYING THE PHYSICAL AND CHEMICAL PROPERTIES OF AMINE AND AMIDE CONTAINING ORGANIC INHIBITORS - Alfiya Oserbaeva; Mohina Muhamadjonova; Shukhrat Bukhorov (American Journal of Applied Science and Technology, 2024)
In this work, new inhibitors of metal corrosion in sulfuric acid environments are studied depending on the duration of the process, inhibitor concentration and temperature. The main parameters for the synthesis of new metal corrosion inhibitors St.3 and St.12 grades using amine and amide containing organic substances are determined and methods for obtaining these inhibitors are described. The physicochemical properties of amine and amide containing organic inhibitors of corrosion and scaling in acidic process environments have been studied.